PENGARUH KESELAMATAN DAN KESEHATAN KERJA TERHADAP KINERJA KARYAWAN PT. SUKA JAYA MAKMUR KABUPATEN KETAPANG - B31110007, AYI AHYANDI (Jurnal Manajemen Update, 2015)
The purpose of this study was to determine how much the influence of occupational safety and health to the employee performance of PT. Suka Jaya Makmur Kabupaten Ketapang. The number of membersÂ  as many as 186 employees. Sampling technique using simple random because we sample member of the population regardless of the strata in the population. And determination of sample size in this study using Slovin formula, in order to obtain the results as many as 65 respondents to be sampled in the study. This study used a descriptive analysis of the quantitative approach using a questionnaire as a data collection tool and using simple linear regression analysis to measure the effect of the independent variables to the dependent variable, which are occupational safety (X1) and health as an independent variable (X2) and employee performance as the dependent variable (Y). The results of this study stated that the occupational safety and health have a significant and positive impact on the performance of employees of PT. Suka Jaya Makmur Kabupaten Ketapang. Keywords : Occupational Safety and Health, Employee Performance